Longitudinal monitoring of BKPyV miRNA levels in kidney transplant recipients with BKPyV‐related pathology reflects viral DNA levels and remain high in viremia patients after clearance of viral DNA. Issue 6 (12th August 2022) - van Doesum, Willem B.; Gard, Lilli; Knijff, Laura W. D.; Niesters, Hubert G. M.; van Son, Willem J.; Stegeman, Coen A.; van den Berg, Anke; Groen, Henk; van den Born, Jacob; Riezebos‐Brilman, Annelies; Sanders, Jan Stephan
Abstract: Introduction: It is unclear whether polyomavirus BK (BKPyV) microribonucleic acid (miRNA) measurement has additional diagnostic and predictive value in kidney transplant recipients (KTR) as compared to current methods of monitoring BKPyV DNA loads. Patients and methods: A retrospective, longitudinal study was performed in 30 KTR with BKPyV viruria ( n = 10), BKPyV viremia ( n = 10), or BKPyV‐associated neuropathy (BKPyVAN) ( n = 10). Bkv‐miR‐B1‐3p and 5p and BKPyV DNA load were measured in urine and plasma and compared using receiver operating characteristic (ROC) curves. Results: Levels of Bkv‐miR‐B1‐3p and 5p and BKPyV DNA correlated strongly. Overall, mostly analog courses of urinary and plasma miRNA and DNA loads were observed. Areas under the ROC curves were not significantly different between miRNAs and DNA. Only, in contrast to BKPyV DNA load, BKPyV miRNA levels increased from 6 to 12 months in the viremia group, while in the BKPyVAN group, a decline was seen in both DNA and miRNA. Conclusions: In this study, we could not demonstrate an additional value of BKPyV miRNA detection compared to BKPyV DNA monitoring in the early phase after kidney transplantation. We did observe significant differences between the viremia and the BKPyVAN groups during follow‐up. This study was performed with a small number of patients and therefore results should be verified in a larger patient cohort. Furthermore, future studies with larger patient groups are necessary to elucidate final clinical value of these data. Abstract :